An unusual cause of dysphagia: a vascular ring. Issue 827 (September 1994) - Hall, R. J.; Treasure, T.
Abstract : A 40 year old woman presented with dysphagia which was due to one of the forms of vascular ring. Her symptoms were relieved by relatively conservative surgery. The means of diagnosis and the surgical approach are discussed.